2002
DOI: 10.1159/000063075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics on Constipation, Fecal Azoreductase Activity and Fecal Mucin Content in the Elderly

Abstract: Background: Constipation is a common problem in elderly subjects, probiotics have been suggested to improve intestinal motility and reduce fecal enzyme activity. Methods: Elderly subjects (n = 28) were enrolled in an open parallel study. The subjects were divided into 3 groups: 1 control group receiving juice; 1 group receiving juice supplemented with Lactobacillus reuteri, and 1 group receiving juice supplemented with Lactobacillus rhamnosus and Propionibacterium freudenreichii. During the first 3 weeks all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 13 publications
5
88
0
1
Order By: Relevance
“…4,5,12,19,20 Our results also revealed a change in the gut flora in patients with FC. The fold differences in the concentrations of Bifidobacterium and Bacteroides spp.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…4,5,12,19,20 Our results also revealed a change in the gut flora in patients with FC. The fold differences in the concentrations of Bifidobacterium and Bacteroides spp.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have suggested probiotics as a possible treatment agent. [12][13][14] The therapeutic outcome of a specific probiotic in the management of patients with FC depends on various factors, including bacterial strains, treatment duration, administration form and dose, and host factors. Currently, due to the paucity of data, whether any particular probiotic is more effective in the treatment of FC remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, independent researches have shown that consumption of P. freudenreichii subsp. shermanii JS decreased to different extents fecal azoreductase activity in elderly subjects, β-glucosidase and urease in healthy young men and β-glucuronidase activity of irritable bowel syndrome patients [202,203].…”
Section: Modulation Of the Host And Resident Microbiota Metabolismmentioning
confidence: 93%
“…bulgaricus and Streptococcus thermophilus produce β-Dgalactosidase thereby improving tolerance to lactose (Adams & Moss, 2000;Fooks et al, 1999, Shah, 2000c Constipation, a disorder of motor activity of the large bowel characterized by bowel movements that are less frequent than normal (Salminen et al, 1998b), pain during defecation, abnormal swelling and incomplete emptying of colon contents (Salminen et al, 1998a), can also be relieved by probiotic use. Lactobacillus reuteri, Lactobacillus rhamnosus and Propionibacterium freudenreichii are probiotic strains shown to improve the condition (Ouwenhand et al, 2002).…”
Section: Therapeutic Benefitsmentioning
confidence: 99%